A governance indicator for small and medium-sized enterprises - Enrique Yacuzzi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2008)
A governance indicator for Small and Medium-Sized Enterprises (SMEs) is presented. The indicator adopts stakeholder theory in selecting its elements, which also include a few general governance principles as well as board features. The paper reviews main governance indicators treated in the literature, which are mostly applied to publicly traded firms. It then proposes a specific indicator for SMEs which, in general, are private. The indicator takes into account - in its structure - the evaluation style of National Quality Awards, as a pattern to measure, by assigning points, a great number of variables. Governance variables included in the indicator are grouped into areas, themes, dimensions and elements, in order to make them operative and measurable. Measurement is performed by means of a questionnaire - reproduced as an appendix - with nominal and interval scales. Maximum scores for each question are assigned following multiple attribute decision theory. The article concludes with reflections on the measurement problem in the social sciences and final thoughts on the characteristics of the proposed indicator. The paper, based on Yacuzzi (2007), is part of an on-going research project. In this new version, several sections of the original work have been improved, others have been deleted, and the questionnaire has been modified in order to incorporate the experience of different users.
Keywords: G34; M10; 330; corporate governance indicator; stakeholder theory; boards; principles of corporate governance; multiattribute decision theory; measurement in the social sciences; KMU; Corporate Governance; Stakeholder